Il pensiero estetico di Nikolaj Evreinov dalla teatralità alla 'poetica della rivelazione' - Claudia Pieralli (Biblioteca di Studi Slavistici, 2015)
This research offers an integral analysis of the aesthetic thought of the director, playwright and art theorist Nikolaj Nikolaevic Evreinov. The work focuses on the analysis of the treaty The revelation of art, written in Paris in the 1930s, which represents the greatest testimony of the author's research in the aesthetic field. Henceforth, a connection is offered between the known aspects of Evreinov's theatrical thought, relating to the period of the avant-garde in Russia, and others, of a broader nature, which have long been precluded from being known. Through insights on the Russian theatrical history of the early 20th century, reflections touching textual criticism, the history of aesthetic thought and Russian criticism, the complex figure of an artist emerges against the background of the culture expressed by post-revolutionary Russian emigration. An artist who, as an intellectual, begins a dialogue with the Western European cultural tradition. This book thus intends to restore the visibility, as well as an exegetical and historiographic completeness, of Evreinov's rich legacy as a writer, a philosopher and a critic.